BIOMEDICAL POTENTIALS OF INTERTIDAL MARINE ORGANISMS FROM SINGAPORE - Alfred Wai Ping Seng; Yan Zhi Ong; Wan Yen Lee; Peter Peng Foo Lee; Swee Cheng Lim; Koh Siang Tan; Lik Tong Tan (JOURNAL OF COASTAL DEVELOPMENT, 2007)
As part of a pilot scale project on drug discovery from local marine organisms, 19 intertidal marine organisms from Singapore waters were collected and screened for the presence of biologically-active natural products. These marine organisms were collected due to the ease of procurement and their relative abundance. The organic extracts of these organisms were prepared and screened in the brine shrimp lethality (BSL), the cytotoxicity (MCF-7 and MOLT-4 cell lines), and the quorum sensing inhibition (QSI) assays. Over 60% of the extracts gave significant biological activities in the BSL and the cytotoxicity (MOLT-4) assays when tested at 1000 ppm. Three sponge extracts showed moderate antibacterial activity while a fraction obtained from the gross fractionation of the extract of the marine cyanobacterium, Lyngbya majuscula (PH2), exhibited anti quorum sensing activity in the QSI assay. Lyngbya majuscula (PH2) also exhibited exceptional biological properties in the toxicity assays and its extract underwent further fractionation. The 1H-NMR spectra of the bioactive chromatographic fractions derived from the microalgal extract indicated the presence of unique lipopeptides. Data from this study provided rationale to initiate marine natural products research for drug discovery in Singapore.